Assessing the sources of reionization: a spectroscopic case study of a 30× lensed galaxy at z ∼ 5 with Lyα, C iv, Mg ii, and [Ne iii]. Issue 2 (13th July 2021) - Witstok, Joris; Smit, Renske; Maiolino, Roberto; Curti, Mirko; Laporte, Nicolas; Massey, Richard; Richard, Johan; Swinbank, Mark
ABSTRACT: We present a detailed spectroscopic analysis of a galaxy at z ≃ 4.88 that is, by chance, magnified ∼30× by gravitational lensing. Only three sources at z ≳ 5 are known with such high magnification. This particular source has been shown to exhibit widespread, high equivalent width C IV λ 1549 A emission, implying it is a unique example of a metal-poor galaxy with a hard radiation field, likely representing the galaxy population responsible for cosmic reionization. Using ultraviolet (UV) nebular line ratio diagnostics, Very Large Telescope (VLT)/X-shooter observations rule out strong active galactic nuclei (AGN) activity, indicating a stellar origin of the hard radiation field instead. We present a new detection of [Ne III] λ 3870 A and use the [Ne III ]/[O II ] line ratio to constrain the ionization parameter and gas-phase metallicity. Closely related to the commonly used [O III ]/[O II ] ratio, our [Ne III ]/[O II ] measurement shows this source is similar to local 'Green Pea' galaxies and Lyman-continuum leakers. It furthermore suggests this galaxy is more metal poor than expected from the fundamental metallicity relation, possibly as a consequence of excess gas accretion diluting the metallicity. Finally, we present the highest redshift detection of Mg II λ 2796 A, observed at high equivalent width in emission, in contrast to more evolved systems predominantly exhibiting Mg II absorption. Strong Mg II emission has been observed in most z ∼ 0 Lyman-continuum leakers known and has recently been proposed as an indirect tracer of escaping ionizing radiation. In conclusion, this strongly lensed galaxy, observed just 300 Myr after reionization ends, enables testing of observational diagnostics proposed to constrain the physical properties of distant galaxies in the James Webb Space Telescope ( JWST )/Extremely Large Telescope (ELT) era.